2008
DOI: 10.1142/s1793048008000861
|View full text |Cite
|
Sign up to set email alerts
|

CADMIUM AND PROTON NMR STUDY ON [Cd2(BIS(2-PYRIDYL)FORMAMINE)3]

Abstract: The structure of a bi - Cd organic complex [ Cd 2(bis(2-pyridyl)formamine)3 or 1], is analyzed thoroughly by 1 H and 113/111 Cd NMR in solution. Only one representative set of pyridyl proton resonance of a total of six pyridines in 1 was observed. The resonance of protons in pyridine ring can be assigned by both 2D COSY and 2D NOESY. Similarly, only one Cd (either 113 Cd or 111 Cd NMR signal was observed too. This indicates that the two Cd atoms in 1 are chemically equivalent. The Cd signal is split by its thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The structure of the complex [Cd 2 (bis(2-pyridyl) formamine] has been solved by using 1 H and 111/113 Cd NMR spectroscopy with the help of long-range 3 J 111CdÀ1H and 3 J 113CdÀ1H couplings, and it is found that both the Cd sites are equivalent with a bridged structure. [73] Such studies might open up new avenues to employ 111/113 Cd NMR spectroscopy to investigate metalloproteins in which the calcium and/or zinc ions present in the active site can be replaced by 113 Cd/ 111 Cd ions of similar size. The use of 2 J( 117 Sn, 1 H) and n J( 31 P, 13 C) in establishing the equivalence or non-equivalence of 13 C sites of organotin(IV) complexes of nicotinamide, isonicotinamide and some of their novel phosphoric triamide derivatives have also been reported.…”
Section: Structure Analysis and Chemical Shift Assignmentmentioning
confidence: 99%
“…The structure of the complex [Cd 2 (bis(2-pyridyl) formamine] has been solved by using 1 H and 111/113 Cd NMR spectroscopy with the help of long-range 3 J 111CdÀ1H and 3 J 113CdÀ1H couplings, and it is found that both the Cd sites are equivalent with a bridged structure. [73] Such studies might open up new avenues to employ 111/113 Cd NMR spectroscopy to investigate metalloproteins in which the calcium and/or zinc ions present in the active site can be replaced by 113 Cd/ 111 Cd ions of similar size. The use of 2 J( 117 Sn, 1 H) and n J( 31 P, 13 C) in establishing the equivalence or non-equivalence of 13 C sites of organotin(IV) complexes of nicotinamide, isonicotinamide and some of their novel phosphoric triamide derivatives have also been reported.…”
Section: Structure Analysis and Chemical Shift Assignmentmentioning
confidence: 99%